ПРОБЛЕМИ ВИКЛАДАННЯ КУЛЬТУРИ РІЗНИМИ МЕТОДАМИ НА УРОКАХ АНГЛІЙСЬКОЇ МОВИ - РАФИЕВА, Эльнура Низами гызы (Вісник Черкаського національного університету імені Богдана Хмельницького. Серія: "Педагогічні науки", 2021)
A methodology is a coherent and stable whole built from elements which have contributed to the selection and the development of a didactic model: the theories of references, the general objectives, the linguistic and cultural contents, the situations of teaching, etc. are among those elements. To this is added a set of techniques, procedures and methods which constitute the set of learning activities that learners will have to carry out in language lessons. Due to many educational, social and political factors and in view of constant scientific progress, the methodologies follow one another and undergo regularly, more or less radically, variations in the principles of teaching and learning. The purpose of the research – the evolution of methodologies makes it possible to understand the place devolved to cultural content according to the didactic and methodological changes that mark the history of methodologies from yesterday to today.